Morphology of bottom surfaces of glacier ice tongues in the East Antarctic region - Bianchi, C.; Chiappini, M.; Tabacco, I. E.; Passerini, A.; Zirizzotti, A.; Zuccheretti, E. (2001)
During three Antarctic summer campaigns (1995/97/99) Radio Echo Sounding (RES) system data from some glacier ice tongues in the East Antarctic regions between Victoria Land and George V Land were collected. The morphology and structure of the bottom surfaces deduced from the electromagnetic interpretation of echo signal were observed. The bottom surfaces at the ice/water interface show either irregular or flat contours or both. Some ice tongues are nearly perfectly flat, others show clear signs of irregularities while three of them have good regular spaced rippled bottom surfaces. The latter structures are well-evident in the longitudinal traverse of the tongues, whereas the transversal paths do not show the same features. This particular shape of the bottom surfaces related to the ablation process and detachment mechanism could be interesting especially to determine some physical characteristics and the possible fracture points of the ice tongues. JCR Journal open